1957
DOI: 10.1111/j.1365-2621.1957.tb16993.x
|View full text |Cite
|
Sign up to set email alerts
|

NUTRITIVE VALUE OF FISHa I. NICOTINIC ACID, RIBOFLAVIN, VITAMIN B12, AND AMINO ACIDS OF VARIOUS SALT‐WATER SPECIES

Abstract: The consumption of fish and other marine products has always been an important factor in the economy and in the nutrition of coastal populations. Recently there has been a trend toward increased fish consumption, particularly in school lunch programs (22, 25, 2 7 ) . Fish cookery demonstrations before school lunch personnel in Maine, New Hampshire, Vermont, Rhode Island, and Connecticut resulted in a 59% increase in fish consumption in the sehool lunch program. It is predicted that one result of this campaign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1960
1960
1980
1980

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…One review (Tarr, 1973) suggests there may be a difference in certain vitamin levels between Pacific and Atlantic Coast fish, and further, cod fish from northern areas may contain more thiamin and riboflavin than from warmer waters (Higashi, 1961). A survey of seafoods common to the New England area (Teeri et al, 1957) indicate lower niacin and riboflavin values than reported herein.…”
Section: Resultscontrasting
confidence: 65%
“…One review (Tarr, 1973) suggests there may be a difference in certain vitamin levels between Pacific and Atlantic Coast fish, and further, cod fish from northern areas may contain more thiamin and riboflavin than from warmer waters (Higashi, 1961). A survey of seafoods common to the New England area (Teeri et al, 1957) indicate lower niacin and riboflavin values than reported herein.…”
Section: Resultscontrasting
confidence: 65%
“…Edible portions of fish muscle were blended and extracted as previously described (3). Vitamin analyses were carried out by standard quantitative microbiological procedure (l), using Lactobacilhls arabinosus 17-5 (A.T.C.C.…”
Section: / Experimental Proceduresmentioning
confidence: 99%